Land-management strategies and the detached housing stock in shrinking municipalities: Evidence from Germany; Landmanagementstrategien und der Einfamilienhausbestand in schrumpfenden Gemeinden: Erkenntnisse aus Deutschland - Andrea Berndgen-Kaiser; Tine Köhler; Maja Lorbek; Markus Wiechert (Raumforschung und Raumordnung / Spatial Research and Planning, 2020)
For some years, increased attention has been paid to the single-family housing stock in Germany and the further designation of building land by municipalities. A Germany-wide anonymous survey of municipalities sheds light on the municipalities' land management strategies with regard to declining populations and their anticipation of future problems for the further use of the single-family housing stock. The results of the quantitative survey are supplemented by qualitative interviews with municipal experts from case studies that were selected on the basis of criteria such as population decline, old-age dependency ratio, the share of single-family homes and vacancy rates. The aims of the survey and the interviews are to assess municipal representatives' perceptions of population decline and of the necessity of undertaking measures to deal with shrinkage. Research questions are: What measures do municipalities consider appropriate to counter population loss and falling demand for housing in shrinking regions? How important are single-family housing areas in the perception of German municipalities? The results indicate that a continued designation of building land seems to be one of the most important measures used to cope with insufficient demand. The aim is to attract new inhabitants, particularly to shrinking cities. However, this approach reinforces current problems because it lowers demand for the housing stock and increases the risk of vacancies. – – Seit einigen Jahren wird der Einfamilienhausbestand in Deutschland und die Praxis weiterer Baulandausweisungen von Kommunen mit erhöhter Aufmerksamkeit betrachtet. Der vorliegende Beitrag gibt Aufschluss über die Landmanagementstrategien von Kommunen vor dem Hintergrund sinkender Bevölkerungszahlen. Die Einschätzung möglicher zukünftiger Probleme für die weitere Nutzung des Einfamilienhausbestandes fußt auf einer anonymen deutschlandweiten Befragung auf der Gemeindeebene. Die Ergebnisse der quantitativen Befragung werden ergänzt durch qualitative Interviews mit Expertinnen/Experten in Fallstudiengemeinden, die nach Kriterien wie Bevölkerungsrückgang, Altenquotient, prozentualer Anteil von Einfamilienhausgebieten und Leerstandsraten ausgewählt wurden. Ziel der Befragung und der Interviews war es zu erfahren, wie die Expertinnen und Experten den Bevölkerungsrückgang einschätzen und ob sie die Notwendigkeit sehen, Maßnahmen gegen Schrumpfung zu ergreifen. Forschungsfragen sind: Welche Maßnahmen halten Kommunen für geeignet, um Bevölkerungsrückgang und rückläufiger Nachfrage bei Einfamilienhäusern entgegenzusteuern? Wie wichtig sind Einfamilienhausgebiete in der Wahrnehmung deutscher Kommunen? Die Ergebnisse deuten darauf hin, dass eine weitere Ausweisung von Bauland eine der wichtigsten Maßnahmen zu sein scheint zur Bewältigung einer unzureichenden Nachfrage, wenn das Ziel ist, neue Einwohnerinnen und Einwohner zu gewinnen, vor allem in schrumpfenden Städten. Dieses Vorgehen verstärkt jedoch die aktuellen Probleme, weil es die Nachfrage nach Bestandsgebäuden senkt und das Leerstandsrisiko erhöht.
Keywords: 710; Detached houses; demographic change; shrinking municipalities; land management strategies; vacancies; village centres; Einfamilienhäuser; demographischer Wandel; schrumpfende Kommunen; Landmanagementstrategien; Leerstände; Ortszentren